Fred or farīd, bacon or bayḍun (‘egg’)? Proper Names and Cultural-specific Items in the Arabic Translation of Harry Potter - Mussche, Erika; Willems, Klaas (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
This paper investigates the transfer of proper names and references to food in the Arabic translation of the first three Harry Potter volumes. The focus of the study is twofold: (1) What is the relation between the different transfer procedures employed in the translation process and the formal, semantic and cultural properties of the source text material? And (2) what is the effect of the applied procedures on the textual and stylistic features of the target text? The major finding that emerges from the investigation is that the main translation strategy is that of simplification. Occasionally, foreignisation is involved as well, but domestication is virtually absent. The findings broadly concur with converging evidence from the translation of other cultural-specific items in the corpus such as references to school and education, kinship and family ties, and the use of dialect and slang, which additionally demonstrate the role of attenuation and normalisation.